Effects of informal economy towards employment : a systematic review - Nor Amaleena Mazlan; Rosilawati Zainol; Yong Adilah Shamsul Harumain (Penerbit Universiti Kebangsaan Malaysia, 2021)
Throughout the years, the ultimate goals of sustainable development are progressing towards reducing poverty and social disparities. In realizing the economic advancement in sustainable development, this paper explores the informal economy's role in creating job opportunities. Few pieces of literature were examined to establish several themes. The existing literature on the informal economy's employment effects was analyzed by employing preferred reporting items for systematic reviews and meta-analyses (PRISMA) review method. Using Scopus and Web of Science as literature search databases, 27 publications have been identified and extracted. These publications were selected based on several criteria, including a timeline, language, publication type and publication stage. Throughout the process, four themes are identified, namely management and regulation, market competitiveness, people's welfare and productivity: with 13 sub-themes, namely regulation for workers, delicensing, local competition, product market, social stability, shelter, economic rights, marginalization, growth, income, tax burden unemployment and investment. These themes are selected through content analysis based on the regularity of these keywords appeared. Few recommendations highlighted the method of studies. Researchers are to conduct more qualitative studies and a standard systematic review technique in guiding data synthesizing. Finally, researchers are to adopt more searching strategies. This paper could contribute to the body of knowledge; in which the PRISMA method is essential for summarizing evidence on the effects of employment in a more accurate manner.